The impact of taxes on the extensive and intensive margins of FDI - Ronald B. Davies; Iulia Traistaru; Zuzanna Studnicka (The Economic and Social Research Institute (ESRI), 2016)
The design of optimal tax policy, especially with respect to attracting FDI, hinges on whether taxes affect multinational firms at the extensive or the intensive margins. Nevertheless, the literature has not yet explored the simultaneous impact of taxation on FDI on these two margins. Using firm-level cross-border investments into Europe during 2004-2013, we do so with a Heckman two-step estimator, an approach which also allows us to endogenize the number of investments and include home country and parent firm characteristics. We find that taxes affect both margins, particularly for firms that invest only once, with 92 percent of tax-induced changes in aggregate inbound FDI driven by movements at the extensive margin. In addition, we find significant effects of both home country and parent firm characteristics, pointing towards the granularity of investment decisions.
Keywords: F23; F14; H25; 330; Foreign direct investment; taxation; extensive margin; intensive margin